NMDA receptors in the insular cortex modulate cardiovascular and autonomic but not neuroendocrine responses to restraint stress in rats - Goulart, Melissa T. (2022)
The insular cortex (IC) is a brain structure involved in physiological and behavioural responses during stressful events. However, the local neurochemical mechanisms involved in control of stress responses by the IC are poorly understood. Thus, this study aimed to investigate the involvement of glutamatergic neurotransmission within the IC in cardiovascular, autonomic and neuroendocrine responses to an acute session of restraint stress. For this, the selective NMDA glutamate receptor antagonist LY235959 (1 nmol/100 nL) or the selective non-NMDA glutamate receptor antagonist NBQX (1 nmol/100 nL) were microinjected into the IC 10 min before the onset of the 60 min session of restraint stress. We observed that the antagonism of NMDA receptors within the IC enhanced the restraint-evoked increase in arterial pressure and heart rate, while blockade of non-NMDA receptors did not affect these cardiovascular responses. Spontaneous baroreflex analysis demonstrated that microinjection of LY235959 into the IC decreased baroreflex activity during restraint stress. The decrease in tail skin temperature during restraint stress was shifted to an increase in animals treated with the NMDA receptor antagonist. Nevertheless, the blockade of either NMDA or non-NMDA glutamate receptors within the IC did not affect the increase in circulating corticosterone levels during restraint stress. Overall, our findings provide evidence that IC glutamatergic neurotransmission, acting via local NMDA receptors, plays a prominent role in the control of autonomic and cardiovascular responses to restraint stress, but without affecting neuroendocrine adjustments.